Analisis Lokasi Optimal Pusat Pemerintahan Dalam Rangka Pengembangan Wilayah Di Kabupaten Buton Tengah Sulawesi Tenggara - HARZAN, Muhamad; , Drs. M. Musiyam, M.T.P; , M. Amin Sunarhadi, S.Si., M.P (2015)
District of Central Buton officially is set to be the new autonomous region on June 24th, 2014 based on the regulation Number. 15th, 2014 it is about the Establishment of District Central Buton in Province of Southeast Sulawesi. With the establishment of the District of Central Buton, the determination of the location of the center of government is very important to support development that is expected to provide a function as optimal service center. The purpose of determining the location of objects is intended to achieve a balance and efficiency. The objectives of this research are: 1) knowing of the most optimal location of the district as government center in Central Buton District based on the method of gravity. (2) Knowing the most optimal location of the district as government center in Central Buton District based on the completeness of facilities and infrastructure development through schallogram method. The result of this research are 1) based on gravity analysis using population weights indicator, the wide area and equal weight the effect of distance showed the same results that the optimal administrative center is the District of Lakudo. (2) schallogram analysis shows that the growth center and services can also be used as the center of government is the District Lakudo. This district has the infrastructure is relatively complete are 17 types and number of units of the largest infrastructure development namely 171 units. Based on the analysis of gravity and schallogram, the District Lakudo is appropriated to become the government center of District of Central Buton